Sildenafil Use in the Treatment of Bronchopulmonary Dysplasia-Associated Pulmonary Hypertension: A Case Series - Amna Qasim; Soham Dasgupta; Ashraf M. Aly; Sunil K. Jain (American Journal of Perinatology Reports, 2018)
Abstract